PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WEB ARTICULATE STORYLINE 3 PADA MATA PELAJARAN IPAS SISWA KELAS IV - Bangun, Novi Olivia; Lidia Simanihuruk; Albert Pauli Sirait; Sri Mustika Aulia; Husna Parluhutan Tambunan (Universitas Negeri Medan, 2025)
This research and development was conducted in class IV of SDN 050628 Tanjung Langkat, based on the problem that teachers had never used interactive learning media, still used concrete media and relied on textbooks, causing students to become bored and unenthusiastic about learning. This research aims to produce a product in the form of web-based interactive learning media using Articulate Storyline 3 for the subject of Science and Mathematics for Grade IV, specifically the material “Changing Energy Forms.” This research is a Research and Development (R&D) study that refers to the ADDIE development model, which consists of five stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The instruments used to measure the quality of the learning media were expert assessment sheets and respondent questionnaires. The results of the study showed that: (1) The validity assessment of the media showed valid criteria with a material expert percentage of 88% and a media design expert percentage of 93%; (2) The assessment of media practicality showed practical criteria based on teacher responses with a percentage of 95% and student responses with a percentage of 92% obtained through questionnaires; (3) The assessment of media effectiveness showed effective criteria as seen in the increase in learning outcomes referring to the N-Gain percentage of 63%. Keywords: Interactive learning media, Articulate Storyline 3 web, IPAS Translated with DeepL.com (free version)